Effects of improving the interactive design of a Chinese character learning system on the learning performance of Chinese as foreign language students. Issue 8 (1st November 2020) - Xu, Yu-Jie; Chiou, Shang-Chia; You, Manlai
Abstract: This study explored interactive interface design for writing practice, feedback, and grading in Chinese character learning systems. In the experiment, 30 novice Chinese learners were invited to perform designated learning tasks on two different learning systems. Learning times and outcomes were measured. The results indicated that improvement of interactive design had positive effects on learning performance, and the participants preferred the interactive design of the newer system. Then, a total of 37 Chinese learners of different proficiencies were invited to complete a survey on their satisfaction toward the interactive design of the new system. The results revealed no significant differences in satisfaction levels across Chinese learners regardless of proficiency; moreover, all participants agreed that the interactive design of the new system benefited their learning. According to the results, improvements in interactive designs can increase learning performance when studying Chinese characters. The results can also serve as interactive design guidelines for future Chinese character learning systems.